Isolation and characterization of cellulose derived from prominent agricultural waste (Sugarcane bagasse) and its utilization in various biomedical field - Sharma, Manoj Kumar; Diwan, Anupama; Sardana , Satish; Yadav, Narender; Gupta, Tanya; Kumawat , Mukesh Kumar (Creative Pharma Assent, 2025)
Background: Agricultural waste clearance and reutilization is a significant problem today. Objective: Successful extraction and purification of cellulose and its derivatives (methylcellulose) from agri-waste and pollution. This is an innovative polymer (cellulose & its derivatives) that can be used in pharmaceutical and technical applications in an eco-friendly manner. Aim: Isolate and characterize cellulose derived from prominent agricultural waste (sugarcane bagasse) and its utilization in various biomedical fields. Method: Eco-friendly Soxhlet extraction utilizing organic solvents was employed to give a high yield of cellulose. Further, the obtained cellulose was bleached and transformed into ester derivatives, such as methylcellulose, to analyze their properties. Result: This study’s primary goal is to concentrate on the production of cellulose and its extraction from different agricultural waste & its characterization. The cellulose isolated from different biomass was comparatively evaluated for its varied properties and was found suitable for use in the pharmaceutical industry or technical dimensions. Conclusion: Agri waste has significant potential and sources for value-based products. Here, successful extraction and derivatization of the cellulose from the sugarcane were done. These extracted celluloses were further subjected to various pharmacopeial, micromeritics, and physiochemical properties assessments, including advanced characterization to evaluate and validate the properties of the products, which signifies more efficient, green extraction and pharmacopeial utilization.